Repeat Flow Diversion for Previously Failed Flow Diversion: Multicenter Experience. (16th November 2020) - Salem, Mohamed M; Sweid, Ahmad; Kuhn, Anna L; Dmytriw, Adam A; Gomez-Paz, Santiago; Maragkos, Georgios A; Waqas, Muhammad; Parra-Farinas, Carmen; Salehani, Arsalaan; Adeeb, Nimer; Brouwer, Patrick; Pickett, Gwynedd; et al.
Abstract: INTRODUCTION: Aneurysmal persistence after flow-diversion (FD) occurs in 5–25% of aneurysms which might necessitate further treatment. A frequently-used retreatment paradigm deploys another flow-diverting stent in a telescoping fashion within the existing device. METHODS: A retrospective review of patients undergoing FD retreatment from 15 centers was performed, with inclusion criteria being repeat FD occurring for the same aneurysm at least 6 months after initial treatment, with minimum of 6 months of imaging follow-up after retreatment. Primary outcome was aneurysmal occlusion, and secondary outcomes were safety and complications. A multivariable logistic regression model was constructed to identify predictors of persistence/occlusion after retreatment. RESULTS: Ninety-five patients (median age 57, 81% females) harboring 95 aneurysms underwent 198 treatment procedures. The majority (87.4%) of aneurysms were unruptured; 74.7% were saccular and 79% were located in the internal carotid artery (median size 9-mm). Median elapsed-time between first and second treatment was 12.2 months. Last available follow-up was performed at median of 12.8 months after retreatment, and median of 30.6 months after initial treatment, showing complete occlusion in 46.2%, and near-complete occlusion (90-99%) in 20.4% of aneurysms. There was no difference in ischemic complications following initial treatment and retreatment (4.2% vs 4.2; P > . 99). On multivariable logistic regression, fusiform morphology was associated with higher odds of non-occlusion after retreatment (OR 7.2; 95%CI 1.97-20.8), with history of hypertension and incorporated branch into aneurysms trending toward incomplete occlusion (OR 3.10; 95% CI 0.98-6.3 and OR 2.78; 95%CI 0.98-6.8; respectively). Family history of aneurysms and positive smoking history were associated with lower odds of non-occlusion (OR 0.18; 95%CI 0.04-0.78 and OR 0.29; 95%CI 0.1-0.86; respectively). CONCLUSION: Repeat flow diversion for persistent aneurysms is safe and effective. Fusiform morphology is the strongest predictor of aneurysmal persistence after repeat flow diversion.